The Role of the Occupational Therapist in Disaster Areas: Systematic Review - M. Parente; M. Tofani; R. De Santis; G. Esposito; V. Santilli; G. Galeoto (Hindawi-Wiley, 2017)
Background. Disasters are increasingly more frequent events on our planet. During disaster the role of the occupational therapist will require a more specific operative framework within nongovernmental organizations and community health services. Design. Systematic review. Objective. The aim of this study is to evaluate the evidence that highlight occupational therapist's role in disaster area through a systematic review. Materials and Methods. Research on MEDLINE was performed. All articles from 2005 to 2015 concerning rehabilitation and occupational therapy in disaster areas were included. Results. Ten studies were selected to be included in this review. Four interesting points emerged: the importance of having rehabilitation intervention in postdisaster situations, the necessity to include a rehabilitation team in the early phase of disaster response, the need to provide a method to address the difficult evacuation, and finding the safest method of transport of people with preexisting disabilities and new injuries. Conclusions. The amount of evidence with respect to specific intervention of the occupational therapist's role in a disaster situation is limited. However some evidence suggests that it could be a good means for reducing the number of medical complications and deaths of persons with preexisting disabilities. The evidences found highlight the necessity to create a multidisciplinary team addressing needs in disasters situation, in which the occupational therapist could certainly contribute.